THE USE OF FORMATIVE ASSESSMENT TOWARD EFL STUDENTS TO ENHANCE STUDENTS’ SELF-EFFICACY IN LEARNING ENGLISH. - Ni Putu Yuni Crisnayanti (Journal of English Language Learning, 2021)
This paper aims to explain the use of formative assessment toward EFL students to enhance students’ self-efficacy in learning English. This paper is descriptive library research. The data of this paper is collected from articles and journals. In this paper, the researcher attempts to explain the use of formative assessment toward EFL students to enhance students’ self-efficacy in learning English. There are several different types of formative assessment that can be applied by teachers in their EFL class to assess the students in which results are expected to enhance the students’ self-efficacy in learning English.